An alternative approach to prepare alginate/acemannan 3D architectures - Silva, Simone S. (2019)
Current research has explored biomedical applications using polymers and compounds derived from plant sources. In the present work, the interactions between acemannan, the main polysaccharide of aloe vera leaves, and alginate, a marine origin polymer were investigated to design biomaterials. As a proof-of-concept, alginate/acemannan beads were produced through an extrusion dipping method followed by freeze-drying technique to form porous beads. Characterization data confirmed that the Ca2+ presence in acemannan composition resulted in a stronger interaction between alginate and acemannan promoting gel formation and further the development of beads with a micro/nano roughness on their surface and heterogeneous porous formation in their interior. Results obtained until now suggest that the present approach represent a feasible and straightforward platform to design 3D biomaterial architectures for biomedical applications.